Time to death and its predictors among neonates who were admitted to the neonatal intensive care unit at tertiary hospital, Addis Ababa, Ethiopia: Retrospective follow up study - Menalu, Mulat Mossie; Gebremichael, Bereket; Desta, Kalkidan Wondwossen; Kebede, Worku Misganaw; Tarekegn, Fetene Nigussie; Mulu, Getaneh Baye; Atinafu, Bantalem Tilaye (Frontiers in Pediatrics, 2022)
Backgrounds: Neonatal death is the major problem in developing world. Burden and predictors of neonatal mortality vary across countries and even among regions of a country, so understanding the problem concerning these factors is essential to overcome the problem. Therefore, this study aimed to determine time to death and its predictors of neonatal mortality among neonates who were admitted to the neonatal intensive care unit of Tertiary Hospital, Addis Ababa, Ethiopia. Methods: A hospital-based retrospective cohort study was employed among 434 neonates admitted in Tertiary hospital, Addis Ababa, Ethiopia. A Kaplan Meier curve and a log-rank test were used to estimate the survival time and compare survival curves between variables. The cox proportional hazard model was also fitted to identify predictors. Results: A total of 434 neonates included in the study, 11.1%] of which were died, and the incidence rate was 19.2 per 1000 live births. The time to death of neonates was 17 days. Independent predictors of neonatal mortality were incomplete maternal antenatal follow up[AHR: 3.7 [95% CI:1.86,7.60]], low(Appearance, Pulse, Grimly, Activity, and Respiration(APGAR)score[AHR:5.0 [95%CI:1.51-15.04]], perinatal asphyxia [AHR:5.2 [95%CI:1.92-14.30]], preterm 4.2[95%CI: 1.32-8.83]]. Moreover, small for gestational age [AHR:4.8[95%CI:2.33-9.72]], respiratory distress[AHR: 2.5[95%CI: 1.24- 5.09]], sepsis [AHR: 3.4[95%CI: 1.71-4.01]], low birth weight [AHR: 7.3[95%CI:2.69,1.91], tracheoesophageal fistula [AHR: 2.2[95%CI: 1.13-4.32]]. Conclusion: The overall incidence rate was 19.2 deaths per 1000 live births. Emphasis should be given to incomplete Antenatal care follow up, small for gestation, preterm, low birth weight, low 5th minute APGAR score, neonatal sepsis, respiratory distress, perinatal asphyxia, and tracheoesophageal fistula.